Pengembangan LKPD Pada Materi Sistem Pencernaan Terintegrasi Nilai-Nilai Islam Untuk Meningkatkan Berpikir Kritis Siswa Kelas XI - Siregar, Handayani; Rasyidah; Khairuna (Universitas Cokroaminoto Palopo, 2024)
This research was motivated by the limited learning resources used by students and the lack of teacher ability in developing teaching materials in the form of LKPD. Apart from that, the teaching materials used in learning have not been integrated with Islamic values, causing a lack of student activity and interest in learning. The aim of this research is to produce teaching materials in the form of LKPD on Integrated Digestive System Material with Islamic Values ​​to Improve Critical Thinking in Class XI Students that are valid, effective and practical. This research is development research (R&D) using the 4D model (Define, Design, Develop, and Disseminate). The validity of the LKPD is obtained from the validation sheet. The validity of the LKPD in the media aspect got a percentage of 91.34%, in the material aspect it got a percentage of 85% and in the Islamic integration aspect it got a percentage of 83.33%. The practicality of LKPD is obtained from teacher response questionnaires and student responses. The practicality of the teacher response questionnaire obtained a percentage of 73.3% and the practicality of the student response questionnaire obtained a percentage of 98.7%. The effectiveness of the LKPD was obtained by pretest and posttest with an n-Gain value of 0.96 with a percentage of 96%. From these